Coincident Observations by the Kharkiv IS Radar and Ionosonde, DMSP and Arase (ERG) Satellites, and FLIP Model Simulations: Implications for the NRLMSISE‐00 Hydrogen Density, Plasmasphere, and Ionosphere. Issue 16 (28th August 2018) - Kotov, D. V.; Richards, P. G.; Truhlík, V.; Bogomaz, O. V.; Shulha, M. O.; Maruyama, N.; Hairston, M.; Miyoshi, Y.; Kasahara, Y.; Kumamoto, A.; Tsuchiya, F.; Matsuoka, A.; et al.
Abstract: This paper reports the results of ionosphere and plasmasphere observations with the Kharkiv incoherent scatter radar and ionosonde, Defense Meteorological Satellite Program, and Arase (ERG) satellites and simulations with field line interhemispheric plasma model during the equinoxes and solstices of solar minimum 24. The results reveal the need to increase NRLMSISE‐00 thermospheric hydrogen density by a factor of 2. For the first time, it is shown that the measured plasmaspheric density can be reproduced with doubled NRLMSISE‐00 hydrogen density only. A factor of 2 decrease of plasmaspheric density in deep inner magnetosphere ( L ≈ 2.1) caused by very weak magnetic disturbance ( D st > −22 nT) of 24 December 2017 was observed in the morning of 25 December 2017. During the next night, prominent effects of partially depleted flux tube were observed in the topside ionosphere ( 50% reduced H + ion density) and at the F2‐layer peak ( 50% decreased electron density). The likely physical mechanisms are discussed. Plain Language Summary: Our planet is surrounded by an extensive envelope of hydrogen gas that stretches a quarter of the way to the moon. It is called the geocorona because it can be seen in ultraviolet light analogous to the corona surrounding the sun during a total eclipse. This hydrogen gas is the source of ionized hydrogen that forms the plasmasphere, which is important because it affects radio wave propagation and therefore the accuracy of global positioning systems. The ultimate source of the hydrogen is the dissociation of water vapor near 100‐km altitude. Both the geocorona and plasmasphere have their source from the atomic hydrogen near 500 km in the thermosphere. For almost half a century, scientists have been using hydrogen density deduced from the observations of Atmospheric Explorer satellite missions. Our study with Kharkiv incoherent scatter radar shows that the hydrogen density is actually 100% higher than the earlier measurements. This result is supported by independent observations with satellites. Our finding means that many of calculations related to the important aspects of space weather influence need to be revisited. And, in a broader sense, our result points the way to better understanding of long‐standing unresolved problems of solar‐terrestrial interaction. Key Points: The NRLMSISE‐00 model underestimated thermospheric hydrogen density by 100% during 2016‐2018 An unusually strong response to the minor storm of 24 December 2017 was observed from the inner plasmasphere to the F2‐layer peak region The Kharkiv IS radar results are consistent with ionosonde, DMSP, and Arase (ERG) satellite measurements